An Exospheric Temperature Model Based On CHAMP Observations and TIEGCM Simulations. Issue 2 (17th February 2018) - Ruan, Haibing; Lei, Jiuhou; Dou, Xiankang; Liu, Siqing; Aa, Ercha
Abstract: In this work, thermospheric densities from the accelerometer measurement on board the CHAMP satellite during 2002–2009 and the simulations from the National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model (NCAR‐TIEGCM) are employed to develop an empirical exospheric temperature model (ETM). The two‐dimensional basis functions of the ETM are first provided from the principal component analysis of the TIEGCM simulations. Based on the exospheric temperatures derived from CHAMP thermospheric densities, a global distribution of the exospheric temperatures is reconstructed. A parameterization is conducted for each basis function amplitude as a function of solar‐geophysical and seasonal conditions. Thus, the ETM can be utilized to model the thermospheric temperature and mass density under a specified condition. Our results showed that the averaged standard deviation of the ETM is generally less than 10% than approximately 30% in the MSIS model. Besides, the ETM reproduces the global thermospheric evolutions including the equatorial thermosphere anomaly. Key Points: An empirical exospheric temperature model (ETM) is developed The thermospheric evolutions of temperature and mass density are well characterized by the ETM The ETM can be embedded in the empirical model to provide better specification of the thermospheric variations